Development of a palliative end of life care (PEOLC) model based on transcultural nursing for patients in need of long-term care - Israfil, Israfil; Buntari Agustini, Ni Luh Putu Inca; Swarjana, I Ketut; Suyasa, I Gede Putu Darma (Universitas Airlangga, 2025)
Introduction: Palliative end-of-life care (PEOLC) is heavily impacted by culture and always discusses death, bereavement, uncertainty, loss, grief, and incurable disease. Long-term care and more culturally sensitive nursing care are essential to address the diverse needs of patients. This study aimed to develop a PEOLC model grounded in transcultural nursing principles, with a focus on enhancing the quality of care for patients requiring long-term support. Methods: This study employed a cross-sectional explanatory design involving 180 patients with chronic illnesses as participants selected using simple random sampling. The proposed model involved eight variables: patient factors, nurse factors, service factors, family factors, technology factors, the PEOLC model, quality of life, and quality of death. A valid questionnaire was used to collect data, and we employed SEM-PLS to analyse the results. Results: The PEOLC model had an R2 value of 0.61. These findings showed that 60.1% of the variability of PEOLC variables was explained by the patient, family, nurse, service, and technology aspects. For each construct, a value of Q2 > 0 (0.083) indicated that the model was appropriate. The path coefficient value of 0.343 indicates that the service factors make the most significant contribution to the PEOLC model. Conclusions: This research led to the development of the PEOLC model, which comprises eight variables. It provides a comprehensive framework for integrating transcultural nursing principles into long-term care and emphasises the importance of cultural sensitivity in delivering personalised and effective end-of-life care.